How to Subvert your University’s Canned Curriculum - Young, Jennifer J. (Radical Teacher, 2018)
The article offers a brief "how-to" guide for getting around canned curriculum while still ensuring that your students learn the course content. It also includes caveats, trouble-shoots, and a justification for subverting requirements to teach standardized curriculum.